Food shelf life stability - Kilcast, David (CRC Press LLC, 2011)
Issues concerning consumer safety, product quality and profitability, predicting shelf-life accurately, various factors which determine shelf-life and the strategies to extend the shelf-life of a product are addressed in this book.